(untitled) (Research, Society and Development, 2021)
The aim of this study was to identify variables associated with early childhood caries (ECC) in 5-year old Brazilian children to allow their monitoring at both regional and national levels. It is a population-based cross-sectional study with epidemiological and socioeconomic data of 7.217 children included in the National Oral Health Survey (SBBrasil 2010). The dependent variable was untreated caries (component c of cpod). Independent variables were grouped into individual and contextual ones, and multilevel models of Poisson regression analysis were applied. In the country, 49,8% of children aged 5 years presented untreated caries. Among the 5 national regions, prevalence of untreated caries was higher in the North (64,9%) and lower in the Southeast (43,7%). National cpod index was 2,45 (CI 95%: 2,20-2,71) and component c was 2,05 (CI 95%: 1,81-2,29). There was a significant difference between North (3,11; CI 95%: 2,69-3,53) and Southeast (1,68; CI 95%: 1.40-1,95) regions. At individual level, low family income was associated with higher prevalence of untreated dental caries (CI 95%: 2,05-2,88). At contextual level, there was higher prevalence of untreated caries in areas with less access to fluoridated water (CI 95%: 1,04-2,25), less access to primary oral health care (CI 95%: 0,93-0,98), higher population/dentist ratio (CI 95%: 1,04-1,33), and higher percentage of children living in low-income families (CI 95%: 1,18-1,78). Our results indicate that socioeconomic factors were determinant for ECC prevalence, increasing dental treatment needs.